Ultrasonographic anatomy of posterior antebrachial cutaneous nerve in healthy subjects - Woo, Sang Rok; Choi, Jun Ho; Jeong, Ha Mok; Yoon, Joon Shik (Muscle & nerve, 2021)
Introduction/Aims The posterior antebrachial cutaneous nerve (PACN) is one of the cutaneous branches of the radial nerve, and receives sensory input from the posterior arm and forearm. The aim of this study is to describe the ultrasonographic anatomy of the PACN. Methods PACN and its branches were scanned using ultrasonography in 30 healthy volunteers. The distances between the epicondylar line and the bifurcation site of each branch of PACN (A) point of separation of the radial nerve and the PACN, (B) point of separation of the anterior and posterior divisions, (C) point of bifurcation of the posterior division into the epicondylar and anconeus branches), cross‐sectional areas and depths from the skin surface to each nerve at positions A, B, and C were measured. Results The mean distance from the epicondylar line to A, B, and C was 10.01 ± 0.82 cm, 7.46 ± 0.98 cm, and 4.02 ± 1.16 cm, respectively. The mean depth from the skin surface at A, B, and C was 1.00 ± 0.19 cm, 0.72 ± 0.19 cm, and 0.51 ± 0.12 cm, respectively. Discussion Ultrasonographic visualization of the PACN and its major branches was feasible. The reference values in this study may be helpful for more accurate sonographic assessment and electrophysiologic study, and contribute to safer interventions around the elbow region.